PENERAPAN MODEL PEMBELAJARAN KOOPERATIF GIVING QUESTION AND GETTING ANSWER TERHADAP AKTIVITAS BELAJAR DAN HASIL BELAJAR SISWA PADA MATERI MENERAPKAN PROSEDUR KEGIATAN RAPAT - Rosmarintan Sihombing (Universitas Negeri Medan, 2020)
Abstrak: Tujuan penelitian ini adalah untuk mengetahui peningkatan hasil belajar siswa pada mata pelajaran produktif OTKP materi menerapkan prosedur kegiatan rapat di kelas XI OTKP 2 SMK Negeri 1 Sidikalang. Melalui penerapan model pembelajaran kooperatif Giving Question anda Getting Answer. Model pembelajaran kooperatif Giving Question and Getting Answer merupakan salah satu strategi pembelajaran aktif. Penelitian ini dilaksanakan di SMK Negeri 1 Sidikalang pada siswa Kelas XI OTKP Semester II T.P. 2018/2019 yang berjumlah 36 orang. Hasil penelitian diperoleh: (1) Penerapan model pembelajaran kooperatif Giving Question and Getting Answer dapat meningkatkan aktivitas belajar siswa. Hasil obsevasi siklus I diperoleh data bahwa terdapat 30 orang (83,33%) siswa untuk kriteria cukup aktif, dan 6 orang (16,66%) siswa yang aktif. Sementara pada siklus II peningkatan data hasil obsevasi aktivitas siswa menunjukkan 6 orang (16,66%) siswa untuk kriteria cukup aktif, 27 orang (75%) siswa untuk kriteria aktif, dan 3 orang (8,33%) siswa untuk kriteria sangat aktif. (2) Model pembelajaran kooperatif Giving Question and Getting Answer dapat meningkatkan hasil belajar siswa. Pada siklus I diperoleh nilai rata-rata 70,27 dan persentase ketuntasan belajar siswa sebesar 36,11% selanjutnya pada siklus II diperoleh nilai rata-rata 81,38 dan persentase ketuntasan siswa sebesar 88,88% dari jumlah siswa yang telah mencapai standar kriteria ketuntasan minimal. Kata Kunci: model pembelajaran, kooperatif giving question, getting answer, aktivitas belajar, hasil belajar, menerapkan prosedur kegiatan rapat. Abstract: The purpose of this study was to determine the increase in student learning outcomes in productive subjects OTKP material to implement the procedure of meeting activities in class XI OTKP 2 Vocational High School 1 Sidikalang. Through the application of your Giving Question cooperative learning model Getting Answer. The Giving Question and Getting Answer cooperative learning model is one of the active learning strategies. This research was conducted at Vocational High School 1 Sidikalang on Class XI students of OTKP Semester II T.P. 2018/2019 of 36 people. The results are obtained: (1) The application of the Giving Question and Getting Answer cooperative learning model can improve student learning activities. The results of observing the first cycle obtained data that there were 30 people (83.33%) students for the criteria of being quite active, and 6 people (16.66%) students who were active. While in the second cycle the increase in data on the results of observations of student activity showed 6 people (16.66%) students for the moderately active criteria, 27 people (75%) students for the active criteria, and 3 people (8.33%) students for the very active criteria . (2) The Giving Question and Getting Answer cooperative learning model can improve student learning outcomes. In the first cycle obtained an average value of 70.27 and the percentage of students learning completeness of 36.11% then in the second cycle obtained an average value of 81.38 and the percentage of students completeness of 88.88% of the number of students who have reached the criteria standard minimal completeness. Keywords: learning models, cooperative giving questions, getting answers, learning activities, learning outcomes, implementing meeting activities procedures.